Komisi I DPR-RI rapat kerja dengan Menhankam tgl. 13 Desember 1993 dan tgl. 1 Pebruari 1994 (Sekretariat Jenderal, Dewan Perwakilan Rakyat, Republik Indonesia, 1994)
Policy and program on national defense and security; report of a meeting of the 1st Commission of Indonesian Parliament with the Dept. of Defense and Security.